The advertisement calls of Quasipaa shini (Ahl, 1930) (Anura: Dicroglossidae) - Kong, Shen Shen; Zheng, Rong Quan; Zhang, Qi Peng (Zootaxa, 2016)
The genus Quasipaa (Family Dicroglossidae) is currently composed of 11 species distributed in China and Southeast Asia: Quasipaa acanthophora (Dubois & Ohler 2009), Q. boulengeri (Günther 1889), Q. courtoisi (Angel 1922), Q. delacouri (Angel 1928), Q. exilispinosa (Liu & Hu, 1975), Q. fasciculispina (Inger 1970), Q. jiulongensis (Huang & Liu, 1985), Q. shini (Ahl 1930), Q. spinosa (David 1875), Q. verrucospinosa (Bourret 1937), Q. yei (Chen, Qu & Jiang 2002) (Frost 2016). These species are morphologically similar, and their taxonomy is subject to controversy (Che et al. 2009). Analyses of nuclear and mitochondrial genes suggest the genus likely encompass additional cryptic species (Ye et al. 2013). Bioacoustics has contributed to studies on the taxonomy of the genus (Ye et al. 2013; Shen et al. 2015), however, to date, only the advertisement calls of Q. spinosa are known (Yu & Zheng 2009; Chen et al. 2012; Shen et al. 2015). Here, we describe the advertisement calls of Q. shini, which inhabits streams in the southern part of central China(Guizhou, Hunan, Guangxi and Jiangxi) and is characterized by the presence of keratinized skin spines on the lateral surfaces of the body.